Combined soft measurement on key indicator parameters of new competitive advantages for China's export - Taosheng Wang; Hongyan Zuo; C. H. Wu; B. Hu (Financial Innovation, 2021)
The estimation of the difference between the new competitive advantages of China's export and the world's trading powers have been the key measurement problems in China-related studies. In this work, a comprehensive evaluation index system for new export competitive advantages is developed, a soft-sensing model for China's new export competitive advantages based on the fuzzy entropy weight analytic hierarchy process is established, and the soft-sensing values of key indexes are derived. The obtained evaluation values of the main measurement index are used as the input variable of the fuzzy least squares support vector machine, and a soft-sensing model of the key index parameters of the new export competitive advantages of China based on the combined soft-sensing model of the fuzzy least squares support vector machine is established. The soft-sensing results of the new export competitive advantage index of China show that the soft measurement model developed herein is of high precision compared with other models, and the technical and brand competitiveness indicators of export products have more significant contributions to the new competitive advantages of China's export, while the service competitiveness indicator of export products has the least contribution to new competitive advantages of China's export.
Keywords: 650; China's export; Core competitiveness; Export competitive advantage; Fuzzy least squares support vector machine; New competitive advantages; Soft measurement